Analisis Pengaruh Dana Wakaf Produktif Terhadap Perkembangan Usaha Masyarakat Kota Medan Pada Masa Pandemi Covid-19 (Studi Kasus Pada Bwi Sumut) - ABD. Hadi Saputra Pulungan; Sri Sudiarti; Nurul Inayah (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to find out how the Effect of Asset Waqf and Cash Waqf on the Development of Community Businesses in Medan City. The type of research used by researchers is quantitative research with an associative approach. The data used is primary data using a data collection tool in the form of a questionnaire or questionnaire with a total sample of 138 people. The data analysis used was multiple linear regression analysis using the SPSS 16.0 application. The results in this study state that asset waqf has a significant influence on business development with a significance value of 0.003. And cash waqf has a significant influence on business development with a significant value of 0.000. The simultaneous F test shows that the variables of asset waqf and cash waqf have a joint effect on business development with a significant value of. The magnitude of the influence of asset waqf and cash waqf on business development in the R Squere test is 59.5%, while the remaining 40.5% is influenced by other variables outside the research.